DEVELOPMENT OF COMPUTER ENGLISH MODULES BASED ON CONSTRUCTIVISME FOR INFORMATICS ENGINEERING STUDENTS AT UNIVERSITAS DHARMAS INDONESIA - Husni, Rauldatul; Izzah, Inayatil (Inspiratif Pendidikan, 2020)
This research is written to develop English Computer Module based on Constructivism for Informatics Engineering Students. In Informatics Engineering department, graduates are expected to have an ability to speak English in order to compete in their job profession. Therefore, it is considered necessary to compile an English Computer module that is specific to the context and purpose with the students of the Informatics Engineering course. The main purpose of this research is to produce English Computer Module for Informatics Engineering students with valid, practice, and effective. The long term goal of this research is to make Engineering students are able to master English language that can be their provision in order to compete in their job profession. This teaching module developed by Constructivism. This research used Research and Development method of ADDIE (Analyze, Design, Develop, Implement, and Evaluate). This research was conducted in the second semester of Informatics Engineering students. In the analysis stage, it was conducted needs analysis and situation analysis. Design stage was conducted by designing Computer English modules based on tasks, lesson plan, and assessment instrument of Computer English modules. Develop stage was conducted by developing teaching material. Implement stage was conducted by implementing teaching material in Engineering class. Finally, the Evaluate stage was an evaluation of the implementation each stages of ADDIE model. The data in this research were collected by using the validation sheet of teaching material, lesson plan, questionnaires respond of Informatics Engineering English lecturer and Engineering students, and students test result. The result of this English Computer Module based on Constructivism for Informatics Engineering Students is valid, practice, effective criteria and accordance to the Engineering students’ needs.